VIRULENSI JAMUR ENTOMOPATOGEN CORDYCEPS MILITARIS DARI BERBAGAI MEDIA TUMBUH TERHADAP LARVA TIRATHABA RUFIVENA WLK. (LEPIDOPTERA : PYRALIDAE) - Fathullah .; Zahratul Millah; Dewi Hastuti (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2012)
This research was done to know virulence of entomophatogenic fungus from some growth medium to larvae Tirathaba rufivena Wlk. This research was held in Laboratory of soil and agroecology Faculty of Agriculture, Sultan Ageng Tirtayasa University from November 2011 to June 2012. Cordyceps militaris is derived the palm plantation PTPN VIII Cisalak baru garden, District Curug Lebak-Banten. This reserach used non faktorial Completely Randomized Design (CRD) with 3 various medium (corn, rice, brand) and repeated 9 times. Monitoring parameter toward hyphal diameter growth, number of colony, and mortality larvae Tirathaba rufivena. Result show that the best Cordyceps militaris medium culture was rice medium regarding to hyphal diameter growth about 0,53 cm at 7 HSI, 2,01 cm at 14 HSI and 3,31 cm at 21 HSI, number of colonies 446,33, virulence (LT50) 2,5 week and, 55,52% mortality at 2 MSI, 92,57% at 3 MSI dan 100% at 4 MSI.Keyword : Cordyceps militaris, Tirathaba ruvivena,Virulence, Mortality.